IMPROVING THE STUDENTS’ READING SKILL THROUGH TRANSLATION METHOD - Hijril Ismail; Juang Kurniawan Syahruzah; B. Basuki (Journal of English Education, 2017)
The aims of this research are to find out how the implementation of translation can improve the students’ reading skill and how the students’ responses to the use of translation method in the teaching and learning process. This research is a classroom action research. The participant is 39 students. The research instrument used is in the form of observation checklist, test, and questioners. The finding of the research shows that the implementation of translation improves the students’ reading skill in the teaching process and the test result. The result of evaluation which carried out in end of the cycle I obtained that the lowest score is 40 and the highest score is 82 then the average score is 58.1, cycle II gets the lowest score is 50 and the highest score is 85 then the average score is 60,9, and cycle III get the lowest score is 60 and the highest score is 85 and the average score is 65.8. Therefore, it can be concluded that the translation method can improve the students’ reading skill of grade VII D of MTs. Muhammadiyah Yogyakarta and the students’ responses are positive when the teacher applied translation method in teaching and learning process.